THE EFFECT OF GOLD PRICES ON THE INDONESIAN COMPOSITE STOCK PRICE INDEX WITH THE EXCHANGE RATE AS A MODERATING VARIABLE - Rahma, Alya; Nurhayati, Immas; Hurriyaturrohman (Universitas Ibn Khaldun Bogor, 2025)
The result researcher aims to evaluate the impact of gold price fluctuations on the dynamics of the Composite Stock Price Index (JCI) in Indonesia, as well as to examine the role of the exchange of rupiah rate towards the United States dollar is employed as a moderating variable. The background of this research is related to the fluctuating dynamics of global financial markets and the tendency of investors to switch to assets that are considered safer such as gold, especially in times of economic uncertainty and exchange rate volatility. In this study, a moderated regression analysis is employed approach, using daily secondary data for a three-month period (November 2024 - January 2025), which includes gold prices, rupiah exchange rates, and JCI data. The analysis's findings show that the Index of Composite Stock Prices is substantially impacted by the price of gold. Furthermore, the JCI is not much impacted by this exchange rate, and the exchange rate erodes the correlation between the JCI and the gold price's moderating variable. These findings give scholars, investors, and policymakers crucial information for understanding how commodities, currency rates, and stock markets interact as well as for creating investment plans and economic policies that can adapt to shifting global circumstances